A communication manual for ASEAN field information officers - Patron, Josefina S.; Agoncillo, Mary Grace V.; Capul, Belina SB. (Quezon City ASEAN Committee on Culture and Information, 1992)
Purpose: Serves as an up-to-date guide to Communication and Development Communication.
Content/s: Field Information Officer (roles and desired qualities). Communication (fundamentals and Development of). Planning communication campaigns. Communication (approaches and techniques). Communication Assemblies (planning ang organizing). Audio-Visual Mobile Communication projects (planning and organizing). Maintenance, Pre-testing and Evaluation.
Keywords: Communication -- Handbooks, manuals, etc; Information scientists -- Handbooks, manuals, etc